2002
DOI: 10.1046/j.1540-8175.2002.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intraoperative Transesophageal Echocardiography in Heart Transplantation

Abstract: The number of centers that perform heart transplants has increased rapidly in recent years. Although transthoracic and transesophageal echocardiography (TTE and TEE) are utilized frequently to diagnose and manage cardiac complications commonly found in this population postoperatively, little has been written about the routine use of intraoperative TEE. Intraoperative echo is ideally suited to identify acute complications during cardiac transplantation. This can include immediate signs of rejection, valvular ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Despite the fact that some look at TEE as a diagnostic modality with more or less higher complications, the majority of authors realize that TEE would be grossly advised in terms of intraoperative cardiovascular monitoring and patient management, especially in hemodynamic field (15)(16)(17). A study by Almeida revealed 82% TEE satisfaction rate in patients in 1999 (15) and some even raise TEE as one of the greatest advances in direct and fast visualization of structural anatomy of the heart and great vessels in addition to homodynamic and functional evaluation of the cardiovascular system and consequently resulting in perfect formulation of a surgical strategy and decision making (16).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that some look at TEE as a diagnostic modality with more or less higher complications, the majority of authors realize that TEE would be grossly advised in terms of intraoperative cardiovascular monitoring and patient management, especially in hemodynamic field (15)(16)(17). A study by Almeida revealed 82% TEE satisfaction rate in patients in 1999 (15) and some even raise TEE as one of the greatest advances in direct and fast visualization of structural anatomy of the heart and great vessels in addition to homodynamic and functional evaluation of the cardiovascular system and consequently resulting in perfect formulation of a surgical strategy and decision making (16).…”
Section: Discussionmentioning
confidence: 99%
“…Expected changes in ventricular morphology and function include increased wall thickness, paradoxical septal motion, or flattening and decreased septal thickening during systole. 64 However, assessment of diastolic function may be complicated by asynchronous atrial contraction and abnormal flow patterns within the atrium and across the MV. There are multiple factors that influence early graft function including baseline cardiac function and inotropic support before harvest, ischemic time and quality of preservation, reperfusion injury, donor-recipient size matching, preexisting pulmonary hypertension in the recipient and cardiac denervation.…”
Section: Left Ventriclementioning
confidence: 99%
“…Additionally, there is a higher incidence of left atrial thrombi in biatrial cardiac transplant as diagnosed by TEE [96,97], including 15% with evidence of acute arterial embolic events [97]. Other significant findings at the time of transplantation can include a PFO in the donor organ (which would likely be closed at the time of transplant) and clinically significant RV dysfunction and tricuspid regurgitation in the allograft due to increased pulmonary vascular resistance in the recipient [98,99]. The severity of tricuspid regurgitation on postoperative TEE at the time of cardiac transplantation has been shown to predict poor late survival in adult cardiac transplant recipients [99].…”
Section: Echocardiography After Cardiac Transplantationmentioning
confidence: 99%